The last erythrosuchid-a revision of Chalishevia cothurnata from the late Middle Triassic of European Russia - Butler, Richard (2019)
Erythrosuchidae is a clade of early archosauriform reptiles that were large-bodied, hypercarnivorous, possibly apex predators in late Early and Middle Triassic ecosystems following the Permo-Triassic mass extinction. Chalishevia cothurnata from the late Middle Triassic (Ladinian) of Russia, is the stratigraphically youngest known erythrosuchid species, but the holotype and referred material of this taxon has received little study. Here, we provide the first detailed anatomical description of C. cothurnata, including comparisons to other erythrosuchids. Although known from relatively fragmentary material, the anatomy of C. cothurnata is distinctive, including an autapomorphic strongly slanted ventral border of the antorbital fossa. The presence of a large accessory opening (the “accessory antorbital fenestra”) in the skull between the premaxilla, nasal and maxilla, together with the inferred presence of a narrow postnarial process of the premaxilla that articulated with a slot on the nasal, provides strong evidence for a sister taxon relationship between C. cothurnata and the erythrosuchid Shansisuchus shansisuchus from the early Middle Triassic (Anisian) of China. The inferred basal skull length of C. cothurnata was approximately 80 cm, making it one of the largest erythrosuchids known.